Manufacturing Error Effects on Mechanical Properties and Dynamic Characteristics of Rotor Parts under High Acceleration - Jia, Mei-Hui; Wang, Cheng-Lin; Ren, Bin (Chinese journal of mechanical engineering, 2017)
Stress, strain and vibration characteristics of rotor parts should be changed significantly under high acceleration, manufacturing error is one of the most important reason. However, current research on this problem has not been carried out. A rotor with an acceleration of 150,000 g is considered as the objective, the effects of manufacturing errors on rotor mechanical properties and dynamic characteristics are executed by the selection of the key affecting factors. Through the force balance equation of the rotor infinitesimal unit establishment, a theoretical model of stress calculation based on slice method is proposed and established, a formula for the rotor stress at any point derives. A finite element model (FEM) of rotor with holes is established with manufacturing errors. The changes of the stresses and strains of a rotor in parallelism and symmetry errors are analyzed, which verify the validity of the theoretical model. The pre-stressing modal analysis is performed based on the aforementioned static analysis. The key dynamic characteristics are analyzed. The results demonstrated that, as the parallelism and symmetry errors increase, the equivalent stresses and strains of the rotor slowly increase linearly, the highest growth rate does not exceed 4%, the maximum change rate of natural frequency is 0.1%. The rotor vibration mode is not significantly affected. The FEM construction method of the rotor with manufacturing errors can be utilized for the quantitative research on rotor characteristics, which will assist in the active control of rotor component reliability under high acceleration.